Using Judas: what early depictions of Judas Iscariot can tell us about their authors - Matthews, Celia-Jayne (2019)
Whilst the vast majority of Christian scholarship in antiquity focusses on the historical and the theological person of Jesus, as well as Christian discipleship, it is clear that Judas scholarship is in the minority. This dissertation sets out to study and analyse literary depictions of Judas Iscariot in antiquity – here, meaning from the New Testament writings (Paul and the Gospels), and a selection of texts from the first century through to the thirteenth century CE. As well as examining how Judas is depicted in these texts, and what sort of role he plays within the overarching narrative, I will also consider how he is used by early writers in light of particular themes, such as anti-Semitism or anti-Judaism. Whilst most of these texts are by no means scholarly or academic, the literature provides a basis for understanding the role of Judas, and in turn, the Jews, within early Christian understanding.